The relationship between galectin‐3 levels and fragmented QRS (fQRS) in patients with heart failure with reduced left ventricular ejection fraction. Issue 6 (2nd June 2019) - Barman, Hasan Ali; Durmaz, Eser; Atici, Adem; Kahyaoglu, Serdar; Asoglu, Ramazan; Sahin, Irfan; Ikitimur, Baris
Abstract: Background: Fragmented QRS (fQRS) complex is an electrocardiographic pattern which reflects myocardial scarring. We aimed to investigate the relationship between the presence of fragmented QRS (fQRS) on electrocardiogram (ECG) and plasma galectin‐3 levels in patients with heart failure (HF) and severely decreased left ventricular ejection fraction (LVEF ≤ 35%). Methods: We prospectively enrolled 125 symptomatic HF patients (NYHA class II‐III) with severely reduced LVEF (≤35%). fQRS was identified in ECG. Galectin‐3 and N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) levels were measured. Patients were divided into two groups based on the presence ( n  = 40) or absence ( n  = 85) of a fQRS on ECG. Results: Majority of patients were male (87.70%), and mean age was 65.1 ± 11.6. Galectin‐3 and NT‐proBNP levels were found to be significantly higher in the fQRS (+) group compared with the fQRS (−) group (NT‐proBNP 5, 362 ± 701 pg/ml vs. 4, 452 ± 698 pg/ml; p  < 0.001, galectin‐3 607 ± 89.8 pg/ml vs. 509.4 ± 63.5 pg/ml; p  < 0.001). Multivariate analyses revealed galectin‐3 and NT‐proBNP levels are the presence of fQRS on ECG ( p  < 0.001 and p  < 0.001, respectively). The area under the curve using the galectin‐3 level for fQRS was 0.819. Conclusions: fQRS and serum galectin‐3 levels are associated with myocardial fibrosis and are associated with poor prognosis in heart failure. In our study, a positive correlation was found between serum galectin‐3 levels and fQRS on ECG.